Pendidikan Kesehatan Dan Aplikasinya di SD/MI - Widodo, Bintoro (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Health education is part of the overall efforts of health (promotive, preventive, curative and rehabilitative) which focuses on efforts to increase healthy living behaviors. In the concept of health education is an effort to inflence /encourage others (individuals, groups and communities) in order to behave in a healthy life. Operationally in health education are all activities to provide / improve the knowledge, attitudes and practices of communitiesin maintaining and improving health. Health education is synonymous with health counseling because both of them are expected behavior changeoriented which is healthy behaviors, so it has the ability to recognize healthproblems himself, his family and his group in improving health. Health education is a part of health promotion is a process to improve the ability of communities to maintain and improve their health and not just relate themselves to increase the knowledge, attitudes and practices of health, but also increase or improve the environment (both physical and non-physical) in order to maintain and improve health.Keywords: health education, school, environment.